2022
DOI: 10.1002/ece3.9020
|View full text |Cite
|
Sign up to set email alerts
|

Land‐use change shifts and magnifies seasonal variations of the decomposer system in lowland tropical landscapes

Abstract: Deforestation and agricultural expansion in the tropics affect local and regional climatic conditions, leading to synergistic negative impacts on land ecosystems. Climatic changes manifest in increased inter‐ and intraseasonal variations and frequency of extreme climatic events (i.e., droughts and floods), which have evident consequences for aboveground biodiversity. However, until today, there have been no studies on how land use affects seasonal variations below ground in tropical ecosystems, which may be mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…This is in line with the results of the study of Cassagne, Gers & Gauquelin (2003) , who reported that litter C/N ratio is an important factor driving Collembola community composition in particular at high soil moisture conditions. Microorganisms sensitively react to changes in microclimate and litter quality ( Fierer, Schimel & Holden, 2003 ; Rousk & Bååth, 2007 ; Zhang et al, 2013 ; Krashevska et al, 2022 ), changing the available food for Collembola. Some Collembola species inhabiting soil were associated with root biomass indicating that living roots may serve as another factor shaping tropical Collembola communities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with the results of the study of Cassagne, Gers & Gauquelin (2003) , who reported that litter C/N ratio is an important factor driving Collembola community composition in particular at high soil moisture conditions. Microorganisms sensitively react to changes in microclimate and litter quality ( Fierer, Schimel & Holden, 2003 ; Rousk & Bååth, 2007 ; Zhang et al, 2013 ; Krashevska et al, 2022 ), changing the available food for Collembola. Some Collembola species inhabiting soil were associated with root biomass indicating that living roots may serve as another factor shaping tropical Collembola communities.…”
Section: Discussionmentioning
confidence: 99%
“…In the tropics, where seasonal climatic variations are less pronounced, seasonal fluctuations in Collembola density and community composition have been reported in few studies, with also usually lower density in the dry than in the wet season ( Palacios-Vargas & Castaño-Menesesm, 2003 ; Wiwatwitaya & Takeda, 2005 ; Muturi et al, 2009 ). Krashevska et al (2022) also reported that soil microfauna, such as Collembola and Mesostigmata are less affected by seasonal variation as compared to soil macrofauna, such as Coleoptera, Psocoptera, and Diptera. However, little is known on changes in seasonal variations in Collembola communities in land-use change context, i.e ., due to the conversion of forest into agricultural plantation systems, particularly in the tropics.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…5300 hectares (Ebadzadeh et al, 2018). The high quality and commercial value of buds and flowers, rose oil, essential oil, hips, and other by-products encourage farmers to expand the area of rose cultivation by land-use changing, resulting in a negative impact on the unique species-rich natural vegetation type, Juniperus-Amygdalus-Pistacia Shrublands, of this region (Krashevska et al, 2022;Noroozi, 2020). On the other hand, outbreaks or increasing populations of the rose pests and diseases e.g.…”
Section: Introductionmentioning
confidence: 99%